The Effect of Pre-eclampsia (PE) Preventing Nutrition Training Program on Pregnant Women's Nutritional Behaviors - Fahimeh Haghi; Shamsodin Niknami; Sedigheh Sadat Tavafian (Hamadan University of Medical Sciences, 2017)
Background and Objective: Preeclampsia (PE) is the most common complication of pregnancy and one of the top three causes of maternal death. Considering the high prevalence of PE, this study was conducted to determine the effect of nutrition training program for the prevention of PE on the nutritional behaviors of pregnant women in Pol-e dokhtar, Iran, 2017. Materials and Methods: This quasi-experimental study was carried out among 120 pregnant women in their third trimester of pregnancy referred to the healthcare centers of Pol-e dokhtar, Iran, in 2017. The participants were randomly assigned into two groups of intervention and control (60 individuals per group). The subjects were selected through cluster sampling method, and data were collected using a questionnaire developed by the researcher including questions about the participants' demographic characteristics, knowledge, attitude, and function. Data analysis was performed using Chi-squared, Fisher's exact test, independent samples t-test, and paired t-test by the help of SPSS software, version 16. Results: The results showed significant differences between the groups in terms of the level of knowledge, attitude, and function (P<0.001). Additionally, there was a significant difference between the pre- and postintervention scores of knowledge, attitude, and function in the intervention group (P<0.001). Conclusion: Educational intervention was effective in the prevention of PE in pregnant women through changing their nutritional behaviors. Therefore, it is suggested to educate pregnant women; moreover, further studies are recommended to confirm the results.